Satiating A User-Delineated Time Constraints While Scheduling Workflow in Cloud Environments (International Journal of Innovative Research in Computer Science & Technology, 2021)
Cloud computing is used to achieve  sustainability in terms of computing. It reduces energy and  resource consumption. Most of the companies have been  moving their applications to the cloud to reduce power,  energy re-source, and carbon emission. Today's computing  landscape is rapidly shifting toward creating applications to  leverage Cloud platforms to have necessary features such as  elasticity, virtualization, low cost, and pay-per-use. Cloud  computing's rising demand and versatility are achieving  acceptance in the research community as a means of  implementing large-scale electronic systems in the format  of workflows (set of tasks). One of the most important  objectives of this effort is to trim down makespan which is  the total period taken by the resources to complete all  workflow activities. Another foremost objective of this  work is to satiate all the user-delineated time constraints  while scheduling workflow activities.
Keywords: Decisive Path; Zadeh's Max-Min rule; Makespan; Workflow Scheduling